Adult Perceptions of In-Class Collaborative Problem Solving as Mitigation for Statistics Anxiety. Issue 2 (3rd May 2016) - Kinkead, Karl J.; Miller, Heather; Hammett, Richard
Abstract: Two purposes existed for initiating this qualitative case study involving adults who had completed a college-level business statistics course. The first purpose was to explore adult challenges with stress and anxiety during the course: a phenomenon labeled statistics anxiety in the literature. The second purpose was to gain insight into adult perceptions of an instructional methodology that employed collaborative problem solving as an intervention to reduce student anxiety levels. Findings from this research provided valuable insights regarding adult perceptions of statistics and statistics courses. First, 75% of the participants recalled their performance in the course as being challenged by elevated levels of stress and anxiety. We also found a distinct inverse correlation between adult self-perception of math competency and statistics anxiety levels. Also notable were findings that a majority of the adult participants perceived working collaboratively markedly reduced anxiety levels, resulting in improved performance on tasks and assessments.